1995
DOI: 10.1016/0014-5793(95)00188-f
|View full text |Cite
|
Sign up to set email alerts
|

The nitric oxide donors, azide and hydroxylamine, inhibit the programmed cell death of cytokine‐deprived human eosinophils

Abstract: ~bstraet Azide and hydroxylamine release nitric oxide (NO) enzymatically in biological conditions. We observed that both compounds were able to inhibit in vitro the programmed cell death ~ff human eosinophils from peripheral blood. This protective effect could be mimicked by permeable cGMP analogs and by the pbospbodiesterase inhibitor 3-isobutyl-l-methylxanthine. Moreover, the soluble guanylate cyclase inhibitor LY-83583 inhibited in a dose-response manner the effects of the NO donors. Consequently, via the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
71
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 26 publications
10
71
1
Order By: Relevance
“…Thus, NO might be critically involved in eosinophil apoptosis. However, our data are in contrast to previously published work indicating that NO acts as a survival factor for eosinophils (47)(48)(49). A recent report also showed that LPS administration in OVA-immunized and -challenged rats drastically decreased an established airway eosinophilia but in conflict to our results, this suppression was associated with a decreased activity of NOS2 (50).…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, NO might be critically involved in eosinophil apoptosis. However, our data are in contrast to previously published work indicating that NO acts as a survival factor for eosinophils (47)(48)(49). A recent report also showed that LPS administration in OVA-immunized and -challenged rats drastically decreased an established airway eosinophilia but in conflict to our results, this suppression was associated with a decreased activity of NOS2 (50).…”
Section: Discussioncontrasting
confidence: 99%
“…Although studies have shown that NO or related molecules can exert either pro-or anti-apoptotic effects depending on the cell type and stimulus (39,(43)(44)(45)(46)(47)(48)(49), the emerging picture is one where the predominant physiologic effect of NOS is inhibition of apoptosis. For instance, NO inhibits apoptosis in murine splenic B cells, human B cell lines, rat ovarian follicles, and human eosinophils (39,(47)(48)(49). The cellular factors and target proteins that are responsible for the specificity of NO-related effects on apoptosis remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…NO dependent generation of intracellular cGMP has been shown to protect against apoptosis in lymphocytes (Genaro et al, 1995), eosinophils (Beauvais et al, 1995), embryonic motor neurons (Estevez et al, 1998), PC12 cells (Kim et al, 1999) and ovarian follicles (Chun et al, 1995). Exactly how cGMP protects against apoptosis is at present unclear.…”
Section: Cgmp Dependent Mechanismsmentioning
confidence: 99%